1.55 µm range edge-emitting laser diodes based on InGaAs/InGaAlAs superlattice and InGaAs quantum wells. (December 2020) - Rochas, S S; Novikov, I I; Babichev, A V; Gladyshev, A G; Kolodeznyi, E S; Karachinsky, L Ya; Bobretsova, Yu K; Klimov, A A; Shernyakov, Yu M; Zhukov, A E; Egorov, A Yu
Abstract: Two laser heterostructures with active region based on seven InGaAs quantum wells and on InGaAs/InGaAlAs superlattice were grown on InP substrates by molecular beam epitaxy. Both active regions were designed for vertical-cavity surface-emitting lasers of 1535-1565 nm spectral range and had total thickness about 80-90 nm. Characteristics of edge-emitting laser diodes fabricated from grown laser heterostructures were studied and compared.